2003
DOI: 10.1074/jbc.m212554200
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junctional Communication Modulates Gene Transcription by Altering the Recruitment of Sp1 and Sp3 to Connexin-response Elements in Osteoblast Promoters

Abstract: Loss-of-function mutations of gap junction proteins, connexins, represent a mechanism of disease in a variety of tissues. We have shown that recessive (gene deletion) or dominant (connexin45 overexpression) disruption of connexin43 function results in osteoblast dysfunction and abnormal expression of osteoblast genes, including down-regulation of osteocalcin transcription. To elucidate the molecular mechanisms of gap junction-sensitive transcriptional regulation, we systematically analyzed the rat osteocalcin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
147
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 126 publications
(156 citation statements)
references
References 72 publications
8
147
1
Order By: Relevance
“…We have previously shown that Cx43 gap junctions can regulate transcription from a Sp1/Sp3 binding "connexinresponse element" in the osteocalcin proximal promoter (OCN CxRE; Stains et al, 2003). To identify whether the FGF2-Cx43 synergistic effect on transcription is being mediated by Runx2, Sp1/Sp3, or both, we analyzed the effects of Cx43 and FGF2 on the Sp1/Sp3 binding OCN CxRE and the Runx2 cognate (p6xOSE2) luciferase reporters.…”
Section: Synergistic Activation Of Osteocalcin Transcription By Fgf2 mentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that Cx43 gap junctions can regulate transcription from a Sp1/Sp3 binding "connexinresponse element" in the osteocalcin proximal promoter (OCN CxRE; Stains et al, 2003). To identify whether the FGF2-Cx43 synergistic effect on transcription is being mediated by Runx2, Sp1/Sp3, or both, we analyzed the effects of Cx43 and FGF2 on the Sp1/Sp3 binding OCN CxRE and the Runx2 cognate (p6xOSE2) luciferase reporters.…”
Section: Synergistic Activation Of Osteocalcin Transcription By Fgf2 mentioning
confidence: 99%
“…Previously, we have shown that disruption of Cx43 can reduce transcription of the osteocalcin gene in response to This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E08 -10 -1079) on April 1, 2009. treatment with serum by modulating signal transduction (Stains et al, 2003;Stains and Civitelli, 2005b). Ultimately, we showed that disruption of Cx43 function results in a decrease in the magnitude of the extracellular signal-regulated kinase (ERK) activation, resulting in a shift in the transcription factor occupancy of the osteocalcin promoter, decreasing osteocalcin transcription.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations